Arterial complications in classical Ehlers-Danlos syndrome: a case series. Issue 11 (28th May 2020) - Angwin, Chloe; Brady, Angela F; Pope, F Michael; Vandersteen, Anthony; Baker, Duncan; Cheema, Harveer; Sobey, Glenda; Johnson, Diana; von Klemperer, Kate; Kazkaz, Hanadi; van Dijk, Fleur; Ghali, Neeti
Abstract : Background: The Ehlers-Danlos syndromes (EDS) are a group of connective tissue disorders with several recognised types. Patients with a type of EDS have connective tissue abnormalities resulting in a varying degree of joint hypermobility, skin and vascular fragility and generalised tissue friability. Classical EDS (cEDS) typically occurs as a result of dominant pathogenic variants in COL5A1 or COL5A2 . The cardinal features of cEDS are hyperextensible skin, atrophic scarring and joint hypermobility. Arterial complications are more characteristically a feature of vascular EDS although individual cases of arterial events in cEDS have been reported. Methods: A cohort of 154 patients with a clinical diagnosis of cEDS from the UK was analysed. Results: Seven patients (4.5%) with a diagnosis of cEDS (four pathogenic, one likely pathogenic and two variants of uncertain significance in COL5A1 ) who had experienced arterial complications were identified. Arterial complications mostly involved medium-sized vessels and also two abdominal aortic aneurysms. No unique clinical features were identified in this group of patients. Conclusion: There is a possible increased risk of arterial complications in patients with cEDS, although not well-defined. Clinicians need to be aware of this possibility when presented with a patient with an arterial complication and features of cEDS. Long-term management in families with cEDS and a vascular complication should be individually tailored to the patient's history and their family's history of vascular events.